Safety Climate and Safety Behavior in a Steel Industry Company in Peru - Herrera Díaz, Manuel Enrique (2020)
Workers are the main axis of occupational safety and health, which is why companies should direct efforts towards learning more about their human capital, raise their awareness and ensure their participation in preventive safety management. The variables used in this research are occupational safety climate (OSC), safety behaviors (SB) and socio-occupational variables. Reliability was verified using Cronbach’s alpha and the relationships between variables were evaluated using Spearman’s correlation coefficient, t-tests and ANOVA. The main results are 1) the reliability of the constructs, 2) verification of significant and positive correlation between OSC and SB, 3) no causal relationships were found between the socio-occupational variables and OSC and SB, and 4) socio-occupational variables age and time of service influence the variable safety participation (SP) in the workplace.